Utilization of Social Media for Accessing Scientific Information by Livestock Farmers in Karnataka State - Raj, UM Rakshit; Satyanarayan, K; jagadeswary, V; Rathod, Prakash Kumar; Kumar, S Naveen; Mahadevappa, DG (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The agricultural and livestock research, education, and extension are important components for increasing production and meetingthe demands of the growing population with sustainability. In this context, knowledge or information is very critical for improving theproduction under the present extension delivery system in India. Several studies have highlighted emerging ICTs which have the potentialto reach the mass population at a limited time despite traditional media. One such emerging ICT is Social Media, which is utilized bymost of the stakeholders, including farmers around the globe. Hence, for documenting its application for livestock information needsamong the livestock farmers, an ex-post-facto exploratory study was conducted in Southern Karnataka using 108 purposively selectedfarmers, which comprised of 36 farmers each belonging to dairy, poultry and sheep and goat husbandry with pre-tested structuredinterview schedule. Majority of the farmers in each category were aware about social media and possessed social media accountswith highest number of WhatsApp accounts being possessed by the farmers. Social media was utilized for obtaining informationabout latest livestock production and management practices in all the categories. From these findings, it could be elucidated that therespondents predominantly perceived that social media had higher benefits in attaining livestock related information and adoptionof digital knowledge into practice.
Keywords: : Extension education; ICT; Livestock farmers; Livestock management; Social media.